2015
DOI: 10.1371/journal.pone.0116645
|View full text |Cite
|
Sign up to set email alerts
|

Unstable Chromosome Aberrations Do Not Accumulate in Normal Human Fibroblast after Fractionated X-Irradiation

Abstract: We determined the frequencies of dicentric chromosomes per cell in non-dividing confluent normal human fibroblasts (MRC-5) irradiated with a single 1 Gy dose or a fractionated 1 Gy dose (10X0.1 Gy, 5X0.2 Gy, and 2X0.5 Gy). The interval between fractions was between 1 min to 1440 min. After the completion of X-irradiation, the cells were incubated for 24 hours before re-plating at a low density. Then, demecolcine was administrated at 6 hours, and the first mitotic cells were collected for 42 hours. Our study de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…It was reported to be applicable for reliable dose–response estimates up to the 7 Gy of low-LET radiation [36]. Earlier, the dose-dependent increase in X-ray-induced chromosomal damage, such as dicentric chromosomes [37] or micronuclei formation [38], was observed in MRC5 cells at a dose of 0.1–1 Gy, which agreed with our results (the yield of micronuclei after X-ray radiation). A much lower level of micronuclei frequency in the case of UPEB irradiation was shown in our study, compared to X-ray radiation.…”
Section: Discussionsupporting
confidence: 92%
“…It was reported to be applicable for reliable dose–response estimates up to the 7 Gy of low-LET radiation [36]. Earlier, the dose-dependent increase in X-ray-induced chromosomal damage, such as dicentric chromosomes [37] or micronuclei formation [38], was observed in MRC5 cells at a dose of 0.1–1 Gy, which agreed with our results (the yield of micronuclei after X-ray radiation). A much lower level of micronuclei frequency in the case of UPEB irradiation was shown in our study, compared to X-ray radiation.…”
Section: Discussionsupporting
confidence: 92%
“…DNA damage was not detected directly, although other experiments indirectly suggested DNA damage. However Ojima et al [ 14 ] demonstrated that frequencies of dicentric chromosomes in normal human fibroblast cells irradiated with fractionated X-rays were significantly reduced in comparison with those in acutely irradiated cells, though the interval between the fractionated irradiations must be short enough. In that study, the interval between fractions was from 1 to 1440 min, and the authors found that the frequency of dicentric chromosomes did not significantly differ when the interval was varied between 5 and 1440 min.…”
Section: Discussionmentioning
confidence: 99%
“… 55 Using the measurement of dicentric frequency in human fibroblasts after irradiation, researchers were able to investigate the role of dose-rate effect in induction of chromosome aberrations. [ 13 ] In cells irradiated with a single X-ray dose the frequency of dicentrics correlated exponentially with doses higher than 0.2 Gy. Irradiation of cells with a single 1 Gy dose of X-rays resulted in similar rise of frequency of dicentrics as irradiation with fractionated 1 Gy dose (fractionation: 10 × 0.1 Gy; 5 × 0.2 Gy; 2 × 0.5 Gy) given with intervals of 1 min between fractions.…”
Section: Non-targeted Effectsmentioning
confidence: 99%
“…Radiation stimulates DNA damage repair through non-homologous end-joining (NEHJ) 12 , an error prone pathway that can lead to induction of chromosome aberrations, which in turn may cause genomic instability. 13 Genomic instability has been connected to induction of most of the human cancers, however currently the exact mechanism of radiation-induced carcinogenesis is not clear.…”
Section: Introductionmentioning
confidence: 99%